Pathways From Early-Life SES to Dementia Risk in Old Age: The Role of Personality. (30th August 2021) - Sesker, Amanda A; O'Súilleabháin, Páraic S; Lee, Ji Hyun; Aschwanden, Damaris; Luchetti, Martina; Stephan, Yannick; Terracciano, Antonio; Sutin, Angelina R
Abstract: Objectives: This study investigates the association between childhood socioeconomic status (cSES) and risk of cognitive impairment in older adulthood, and whether the Five-Factor Model personality traits mediated this association. Methods: A sample of 9, 995 participants (mean age = 67.01 years) from the Health and Retirement Study were followed up every 2 years from 2006 to 2018. cSES was tested as a predictor of risk of dementia and risk of cognitive impairment not dementia (CIND). Personality was tested as a mediator of these associations. Models were adjusted for age, gender, ethnicity, race, education, and baseline year. Results: Although effect sizes were modest, results indicated that lower cSES was associated with a higher risk of dementia (hazard ratio = 0.88 [0.775–0.985]). Higher cSES was also associated with higher conscientiousness and lower neuroticism. Conscientiousness and neuroticism each accounted for 7.9% of the total effect of cSES on dementia. Results were similar for CIND. Discussion: Early childhood socioeconomic factors may contribute to cognitive impairment in older adulthood, an association mediated, in part, through adult personality traits.